Implementation of BAZNAS Policy Overcoming Poverty and Realizing Community Welfare in Karawang District West Java Province - Eka Sanatha; Khasan Effendy; Sampara Lukman; Andi Pitono (Yayasan Riset dan Pengembangan Intelektual, 2023)
This research discusses the implementation of BAZNAS policies in overcoming poverty and realizing community welfare in Karawang Regency. The aim is to discuss the collection of zakat by BAZNAS to reduce the gap between the zakat obtained and the existing zakat potential, as well as to find new strategies and patterns in the implementation of BAZNAS policies. The research method used is a descriptive qualitative approach. The results of the study indicate that the implementation of BAZNAS policies is quite optimal. This can be seen from the execution of the organization that is supported by competent and integrity Human Resources, the understanding of policy implementers and recipients about the importance of BAZNAS implementation, and the support of an up-to-date integrated system. The new concept generated is about the implementation of structured and patterned policies in the collection and distribution of zakat, as well as the integration of zakat beneficiary data with a priority on effectiveness, ability, and adaptation.